PENGARUH FAKTOR EKONOMI, PENDIDIKAN DAN IKLAN PEMILIHAN PENGOBATAN SENDIRI TERHADAP UNTUK NYERI SENDI OLEH LANSIA DI KELURAHAN MERTELU, GEDANGSARI, GUNUNGKIDUL - , AWALI KARUNIA JATI ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Background: Joint pain is a disease caused by the process of aging, which encourages the elderly to find the medication. Most of them chose self-medication for the treatment. Selfmedication provides advantages and disadvantages. Self-medication which does not fit the rules will increase the rise of side effects. Economy, education and advertisement regarded as some factors that affect the decision in choosing self-medication. Objective: To know the influence of economy, education and advertising on choosing selfmedication of joint pain by elderly in Kelurahan Mertelu Gedangsari, Gunungkidul. Methods: This research is a descriptive analytic study with cross sectional approach. Conducted in March 2014 in Kelurahan Mertelu, Gedangsari, Gunungkidul. The subjects of the research are 57 people who are aged more than 60 years and had done self-medication for joint pain. The samples were taken using proportional random sampling technique. Questionnaire was used as the research tool, and the data was analyzed using chi square test and kolmogorov-smirnov. Results: Respondents satisfied with self-medication that theyâve done. Self-medication is done on the level of mild pain on their own initiative carried out under the pretext of cheap. Previous experience is the source of information on drugs in the self-medication. The bivariate analysis showed that the factors which have value significance (p) < 0.05 is the economic factor (0,020) and education (0,043). Conclusion: Education and economic are the factors that influence the choosing of selfmedication for joint pain by elderly in Kelurahan Mertelu, Gedangsari, Gunungkidul. Keywords: elderly, joint pain, self-medication